Association between hepatitis C virus infection and rheumatoid arthritis: a nationwide cross-sectional study - Lin Tang; Lei Zhang; Zhonghai Ding; Wenying Xu; Yu Liu; Zhenghong Yu (BMC Rheumatology)
Abstract Background Patients infected with Hepatitis C Virus (HCV) often present with rheumatic symptoms, but its link to rheumatoid arthritis (RA) remains unclear. The purpose of this cross-sectional study was to investigate whether HCV infection is related to the risk for RA in adults. Methods We analyzed data from the 2017–2020 National Health and Nutrition Examination Survey (NHANES). HCV infection and RA status were determined through questionnaires. Covariates included gender, age, race, marital status, body mass index (BMI), high-sensitivity C-reactive protein (hs-CRP), and diabetes status. Multivariate logistic regression and subgroup analyses were used to assess the relationship between HCV infection and RA risk. Results In this population-based study involving 5,825 participants aged 18–80 years (including 485 RA patients), we observed a significantly higher prevalence of HCV infection in the RA group compared with non-RA controls. After adjusting for covariates, multivariate logistic regression showed that HCV infection was associated with an increased risk of RA (OR = 1.93; 95%CI = 1.07–3.50, p < 0.05). Conclusion This study demonstrates that HCV infection is associated with the risk of RA in adults, underscoring the potential value of HCV screening in RA patients for improved disease management. However, causal interpretation is limited by the cross-sectional design and reliance on self-reported data.